The importance of local adaptation for sustainable chicken production: the example of Ethiopia - Hanotte, Olivier H.; Trujillo, A.V.; Kebede, A.; Gheyas, Almas A. (2019)
Domesticated in the tropical humid and sub-humid areas of Asia, the indigenous domestic chickens are now found in all agro-ecologies across the world - including temperate, cold, hot and dry environments - where they sustain the livelihood of millions of small-holder farmers. Despite this, the understanding at the genome level of the environmental adaptability of the species is still in its infancy. We will review here, the origin, history and distribution of the genome diversity of the species in light of the geographic distribution of the wild ancestor, the red junglefowl, and related species within the genus Gallus. Then, using Ethiopia as a country example, we will introduce a framework to classify the indigenous chicken population into candidate ecotypes based on environmental niche similarity. Application of this framework on a set of Ethiopian village chicken populations (n = 25) identify 12 different ecotypes laying the ground for genotype-environment association studies.